Extensive Supporting Cell Proliferation and Mitotic Hair Cell Generation by In Vivo Genetic Reprogramming in the Neonatal Mouse Cochlea - Ni, Wenli (J Neurosci, 2016)
The generation of hair cells (HCs) from the differentiation of proliferating supporting cells (SCs) appears to be an ideal approach for replacing lost HCs in the cochlea and is promising for restoring hearing after damage to the organ of Corti. We show here that extensive proliferation of SCs followed by mitotic HC generation is achieved through a genetic reprogramming process involving the activation of β-catenin to upregulate Wnt signaling, the deletion of Notch1 to downregulate Notch signaling, and the overexpression of Atoh1 in Sox2(+) SCs in neonatal mouse cochleae. We used RNA sequencing to compare the transcripts of the cochleae from control mice and from mice with β-catenin activation, Notch1 deletion, and β-catenin activation combined with Notch1 deletion in Sox2(+) SCs. We identified the genes involved in the proliferation and transdifferentiation process that are either controlled by individual signaling pathways or by the combination of Wnt and Notch signaling. Moreover, the proliferation of SCs induced by Notch1 deletion disappears after deleting β-catenin in Notch1 knock-out Sox2(+) cells, which further demonstrates that Notch signaling is an upstream and negative regulator of Wnt signaling. SIGNIFICANCE STATEMENT We show here that the extensive proliferation of supporting cells (SCs) and the subsequent mitotic hair cell (HC) generation is achieved through a genetic reprogramming process involving activation of β-catenin to upregulate Wnt signaling, deletion of Notch1 to downregulate Notch signaling, and overexpression of Atoh1 in Sox2(+) SCs in neonatal mice cochleae. By comparing the transcripts of the cochleae among controls, β-catenin activation, Notch1 deletion, and β-catenin activation combined with Notch1 deletion group, we identified multiple genes involved in the proliferation and transdifferentiation process that are either controlled by individual signaling pathways or by the combination of Wnt and Notch signaling. This provides a better understanding of the mechanisms behind mitotic HC generation and might provide new approaches to stimulating mitotic HC regeneration.